Optimization of Babinsa Performance Improvement In Terms Of Competence, Motivation, and Job Satisfaction (A Study on Babinsa Kodim 1207/Pontianak) - Hamid, Abdul; Romi, Mochamad Vrans (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2026)
The active involvement of Babinsa in territorial development is a key factor in realizing a strong space, tools and conditions for defense to effectively support the main tasks of Kodim at the local level so that Babinsa has a very strategic role in maintaining regional stability and resilience, including Babinsa at Kodim 1207/PTK. In reality, the performance of Babinsa in Kodim 1207/PTK is relatively low. This is due to limitations in the education and training received, the lack of access to or quality of training, which negatively impacts skill development, and the uneven workload distribution, as each Babinsa is generally assigned to only one village. The purpose of this study is to determine the effect of competence, motivation, and job satisfaction on performance. The sampling technique used is simple random sampling. The results of the study show that competence, job satisfaction, and Babinsa's performance are categorized as sufficient, while motivation falls into the low category. The data analysis results indicate that competence, motivation, and job satisfaction have a significant positive effect on Babinsa's performance, both partially and simultaneously. These results suggest that to improve Babinsa's performance, efforts should be made to enhance competence through training and education, increase motivation through various incentive and reward programs, and create a supportive work environment. Thus, a holistic approach that includes the development of competence, motivation, and job satisfaction will have a positive impact on the performance of Babinsa in Kodim 1207/PTK.